2018
DOI: 10.15414/jmbfs.2018.8.1.751-755
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Moringa Oleifera Leaves and Its Utilization as Value Added Ingredient in Unleavened Flat Bread (Chapatti)

Abstract: Micronutrient deficiency is a major concern now a days as more than 30 percent of world’s population is suffering from nutritional deficiency. People are getting awareness regarding food biodiversity, therefore they demand value added and nutritionally enriched food products to counter appetite as well as to improve their health. This study was conducted to assess the nutritional potential of Moringa oleifera leaves powder (MOLP) and a product was developed to ensure its efficient utilization in chapatti (Unle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
3
5
0
Order By: Relevance
“…In general, all composite bread supplementation recorded enhanced phytochemical constituents when compared to control bread (made with 100% flour). These results agree with that reported by Mushtaq et al [34] in their study of characterization of Moringa oleifera leaves and its utilization at 5, 10, 15 and 20% as value added ingredient in unleavened flat bread (chapatti). Total phenol (0.75 to 2.30, 4.82, 6.41 and 8.38) and total flavonoid (0.38 to 1.36, 2.14, 2.98 and 3.66) contents significantly increased with increasing levels of Moringa leaf powder.…”
Section: Effect Of Moringa Oleifera Leaves Supplementation On Phytochemical Properties Of Breadsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, all composite bread supplementation recorded enhanced phytochemical constituents when compared to control bread (made with 100% flour). These results agree with that reported by Mushtaq et al [34] in their study of characterization of Moringa oleifera leaves and its utilization at 5, 10, 15 and 20% as value added ingredient in unleavened flat bread (chapatti). Total phenol (0.75 to 2.30, 4.82, 6.41 and 8.38) and total flavonoid (0.38 to 1.36, 2.14, 2.98 and 3.66) contents significantly increased with increasing levels of Moringa leaf powder.…”
Section: Effect Of Moringa Oleifera Leaves Supplementation On Phytochemical Properties Of Breadsupporting
confidence: 93%
“…The enhanced levels recorded in composite bread is due to naturally occurring antioxidants present in the Moringa leaves. These results as regards FRAP and DPPH are consistent with that reported by Mushtaq et al [34] where they recorded wide variation in DPPH scavenging activity of Chapattis sample. Addition of Moringa oleifera leaves powder increased antioxidant percentage with maximum value observed in 20% (64.32% to 80.52%).…”
Section: Effect Of Moringa Oleifera Leaf Supplementation On Antioxidant Properties Of Composite Breadsupporting
confidence: 92%
“…The cooking process caused a significant decrease in the TPC values in all samples ( P < 0.05) and the most significant reduction occurred in cooked M5 pasta – about 40% when compared to the uncooked counterpart. As reported in the literature, the reduction of TPC in cooked pasta could be due to the degradation of polyphenols during the boiling treatment or to the leaching of some polyphenols (mainly from the free fraction) into the cooking water 20‐24 . However, considering a medium uncooked pasta serving of 100 g, current data indicated that with M15 the TPC intake is about 444 mg.…”
Section: Resultsmentioning
confidence: 68%
“…The TPC of MOLP was 62.71 ± 1.87 mg GAE g −1 of DM and represent an intermediate value between the TPC content of MOLP (88.63 ± 1.90 mg GAE g −1 of DM) used for Chapatti 23 and the one used for bread 24 (33.13 ± 2.39 mg GAE g −1 of DM) fortification, respectively. In addition, the antioxidant capacity of MOLP measured by FRAP and ABTS assays was 232.22 ± 9.53 μmol L −1 TE g −1 DM and 84.40 ± 3.73 μmol L −1 TE g −1 DM, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, this paper proposes to use the unsold remnants of cereal dishes (porridge) in the production of bakery products at the same catering enterprise. In turn, bakery products are one of the favorite and preferred snacks of consumers [3,5,6,7]. The proposed solution will not only enrich the flour products, but also reduce the technological cycle of their production, thereby reducing energy costs in their production, as well as the use of residues from unreleased products for the day.…”
Section: Introductionmentioning
confidence: 99%